Micronized apple pomace as a novel emulsifier for food O/W Pickering emulsion. (15th November 2020) - Lu, Zhiqiang; Ye, Fayin; Zhou, Gaojuan; Gao, Ruiping; Qin, Dingkui; Zhao, Guohua
Highlights: Nano/micrometer size apple pomace particles were successfully obtained by milling. Apple pomace particles at different sizes exhibited different basic properties. Pickering emulsions stabilized by apple pomace particle were successfully fabricated. Emulsion formed by smaller particle had better physical and oxidative stability. Abstract: In order to develop natural, food-grade particles as emulsifiers, wet-milled has been conducted to obtain apple pomace particles in varying sizes. Structural characteristics, physicochemical properties and Pickering emulsifying potential of the particle in different sizes were investigated. Particle size of apple pomace was gradually reduced from 12.9 μm to 550 nm during 8 h milling. With the decrease of particles size, the morphology became less angular. Meanwhile, some insoluble dietary fibers transformed into soluble ones, and the wettability tended to be hydrophilic, therefore, the water and oil holding capacities and free-radical-scavenging capacities increased. The properties of Pickering emulsions stabilized by wet-milled apple pomace particles in different sizes were then investigated. The decrease of particle size resulted in the size reduction of emulsion droplets, and gave rise to enhance gel-like properties and antioxidative activities of emulsions. The results demonstrated promising prospect of wet-milled apple pomace particles as emulsifiers in food industry.